Trends in socio-demographic characteristics and substance use among high school learners in a selected district in Limpopo Province, South Africa - Linda Shuro; Firdouza Waggie (BMC, 2024)
Abstract Background Substance use is an escalating public health problem in South Africa resulting in risky behaviours and poor educational attainment among adolescents. There is a huge battle to overcome substance use among learners as more drugs become easily available with the mean age of drug experimentation reported to be at 12 years of age. It is important to continuously understand the trends in substance use in order to assess if there are positive changes and provide evidence for the development of context-specific effective interventions. This paper outlines the prevalence of substance use among selected high schools in a district in Limpopo province. Methods To determine the prevalence of substance use among selected high school learners in a district in Limpopo Province, a cross-sectional school survey of 768 learners was conducted. Data was analysed using SPSS v 26. Descriptive analysis was used to describe the independent and dependent variables and Chi-Square test was used to investigate associations between demographic characteristics and substance use among high school learners. Results The most abused substances by learners were alcohol (49%), cigarettes (20.8%) and marijuana (dagga/cannabis) (16.8%). In a lifetime, there was a significant difference (P < 0.05) in cigarette smoking with gender, school, and grade; with more use in males (14.2%) than females (7.6%); in urban schools (14.6) than peri-urban (6.7%) and more in Grade 12 (6.4%). There was a significant difference (P < 0.05) in alcohol use with more use in Grade 10 (12.6%) and varied use among male and female learners but cumulatively more alcohol use in females (27.7%). Drug use varied, with an overall high drug use in urban schools (20.7%). Conclusions Substance use is rife among high school learners in the district and health promotion initiatives need to be tailored within the context of socio-demographic characteristics of learners including the multiple levels of influence such as peer pressure, poverty, unemployment and child headed families. Additional research is required to investigate the factors leading to a notable gradual increase in use among female learners and into the environmental and family settings of learners in influencing substance use.